From “imbecile” to “Peace of the Lord”: sense effects on a religious live from preacher’s subject-position - Silva, Dalexon Sérgio da; Cavalcanti, Maria do Carmo Gomes Pereira (Revista Letras Raras, 2022)
This paper analyzes a video, which was published on the uol website, on September 19th 2020, in which a preacher makes a religious live addressing to his congregation; however, without knowing that the recording had already started, he promotes two antagonistic statements. First, when imagining that the camera was turned off, he harasses his wife by calling her "an imbecile". Then, imagining that the camera was on from that moment on, he greets his listeners with "embrace the Peace of the Lord." Thus, in light of the theoretical perspective and analytical procedures of the French Discourse Analysis (FDA), based on the Pêcheux studies in France, Orlandi and scholars in Brazil, this work aims to analyze these two statements published in video, crossed by historicity and by ideological functioning. To this end, it mobilizes the concepts of subject, discursive formation, sense effects and discursive memory, observing that the camera used for a live, is not only shown as a filming object of a social event, but works through the constitutive exteriority, as a socio-historical symbolic object that marks the presence of at least two antagonistic discursive formations in which the pastor subject presents in the thread of his discourses, promoting different meaning effects in new discourses.